A Comparative Analysis of Reader’s Preference Over e-book vs Physical Fiction Books in Ahmedabad City - Pandya, Kishan; Patel, Ripal; Vidani, Jignesh (Contemporary Journal of Applied Sciences, 2024)
This study examines the preferences of readers in Ahmedabad city for e-books over physical fiction books, focusing on age as a determining factor. Data collected through a structured survey revealed important insights into how age shapes opinions on these aspects. The findings suggest that e-books are highly preferred for their portability, especially among younger readers, while physical books remain universally preferred for their immersive experience and cultural value. The study highlights the balanced coexistence of physical and digital reading formats, driven by factors beyond age, such as personal habits, accessibility, and cultural sentiments. The findings have implications for publishers, booksellers, and policymakers, emphasizing the need for hybrid strategies that cater to diverse reader preferences. Recommendations include targeted marketing, sustainable practices, and literacy initiatives to support both formats